About the cult of bear among Tofalars - Rassadin, Valentin I. (The New Research of Tuva, 2013)
Article analyzes the details in naming the bear in Tofa language and draws parallels with other languages of indigenous people of the North. It comes to the conclusion of an ancient cult of bear in the culture of Tofalars.
Keywords: Tofalars; Tofa language; bear; cult of bear; hunting traditions